From Gated-Community to Gated-Neighbourhood: The Case of a Housing Estate Bank in Mavişehir, Izmir - Gürman, Aysu; Buldan, Ece (Nakhara : Journal of Environmental Design and Planning, 2024)
Gated-communities have appeared as a housing strategy within the capitalist system. This study employs Lefebvre’s understanding of spatial production to conceptualize gated-communities as abstract spaces and explore their effects on the built environment, which extends in scale from the individual home to the neighbourhood. The opted methodology for the study is a literature review and critical interpretation of theoretical studies on this field by focusing on the Mavişehir neighbourhood in İzmir. This neighbourhood, with multi-story buildings and villas, attracts senior and upper-middle-income residents seeking security and prestige. The area offers shopping malls, sports centres, schools, and open spaces in addition to gated communities. Investigating the impact on the surroundings of the first resident construction, Mavişehir Emlak Bank Residences, the study explores how the neighbourhood has been transformed into a commodity, fostering a gated-neighbourhood concept that inherently defines the specific patterns of social relations in the city.